Women career advancement in public service: A study in Indonesia - Abdul Ghani Azmi, I.; Syed Ismail, S.H.; Basir, S.A. (2012)
There are lots of facilities provided by the Indonesian public service to the Muslim women public servant to ease the effect of working on their families such as child care, job sharing, flexible hours, longer maternity leave and working from home. On top of that, policies available that support the women are treating them with the same trust and confidence, giving them the same assignment, paying them comparable salaries as men and not to relocate them for the sake of career advancement. It is found out that the factors that contribute to their career success were experience, education, seniority, interpersonal skills, ability in tackling superiors, commitment and dedication, support from superiors, colleagues and family and leadership styles. On the other hand, they believe that there are some factors that hinder them from career advancement which are preference for family, limited access to professional training, personality, lack of leadership charisma, lack of confidence, society expectation, gender bias, lack of qualification; power; prestigious developmental assignments and informal network, no mentoring system, low self esteem and not taken seriously. They believe that Muslim women are capable in leading organizations as physical inferiority compared to men is not a factor in their religion. In fact, they should be obeyed and respected as men as their religion does not prohibit them to be the leader of men in general. This is due to gender is not a factor but their capabilities are. Moreover, Indonesian Muslim women public servants are more concerned of their staff. However, family is more important than their career. Thus, these Indonesian public servants believe that Muslim women should assist their family financially if the husbands are unemployed or terminally ill. Majority agreed that they have good prospects for promotion in their departments. Hence, they would apply promotion in the next three to five years. In order to get the promotion, they are willing to devote their time to advance in their career such as to further studies, perform abilities, attend courses, develop network with management or change leadership style. Majority of them would also like to adjust their career aspiration if they are unsuccessful in their career advancement. However, only one of them would like to leave the organization.